A new cutting force model for predicting stability of interrupted turning. (June 2015) - Chen, L. H.; Xu, Y. W.; Zhang, L. H.; Man, J.
<x content-type="archive" xml:space="preserve">Abstract</x> A new non-linear dynamic cutting force model considering nominal chip thickness is presented for predicting the stability of interrupted turning, in where the non-linear dynamic cutting force is described through a non-linear function of nominal chip thickness and dynamical chip thickness. Stability lobe considering nominal chip thickness of interrupted turning is obtained based on semi-discretization method and Floquet theory. Both numerical and experimental tests demonstrate that there is a strong correlation between the nominal chip thickness and the interrupted turning stability, and the proposed model is proved effective for the interrupted turning process.